Task specialization, immigration, and wages - Giovanni Peri; Chad Sparber (University of California, Department of Economics, 2008)
Many workers with low levels of educational attainment immigrated to the United States in recent decades. Large inflows of less educated immigrants would reduce wages paid to comparably-educated native-born workers if the two groups are perfectly substitutable in production. In a simple model exploiting comparative advantage, however, we show that if less educated foreign and native-born workers specialize in performing different tasks, immigration will cause natives to reallocate their task supply, thereby reducing downward wage pressure. We merge occupational task-intensity data from the O*NET dataset with individual Census data across US states from 1960-2000 to demonstrate that foreign-born workers specialize in occupations that require manual and physical labor skills while natives pursue jobs more intensive in communication and language tasks. Immigration induces natives to specialize accordingly. Simulations show that this increased specialization might explain why economic analyses commonly find only modest wage and employment consequences of immigration for less educated native-born workers across US states.
Keywords: F22; J61; J31; R13; 330; Immigration; less-educated labor; manual tasks; communication skills; comparative advantages; US states